Examining the Authenticity of Tafsir al- Jailani as the Work of Abdul Qodir Jailani - Munji, Ahmad (JURNAL PENELITIAN, 2019)
This paper attempted to discover the authenticity of interpretation work ordinated to Abdul Qodir Jailani. This interpretation Sufism was published by two different publishers from two separate countries; Dar alKutub al-Ilmiyah located in Beirut, Lebanon and Markaz al-Jailani li al-Buhus al-Ilmiyah in Istanbul, Turkey. This research is conducted from incredulity of ordination validity towards that interpretation work (Tafsir). By reason that the script was similar to another spread-script whose title is Fawatih al-Ilahiyah authored by Baba Ni’matullah Najwani. By comparison to two versions of Tafsir al-Jailani and one version of al-Fawatih al-Ilahiyah, this research comes to conclusion that this Tafsir (Tafsir al-Jailani) is inscription of Baba Ni’matullah Najwani, not Abdul Qodir al-Jailani. This conclusion goes against to three points; first, the name in book cover is not compatible with the name in introduction as the author had conveyed it in this Tafsir’s introduction; Second, the Author discussed many topics about Wahdat alWujud, a Sufism terminology acknowledged by Ibn Arabi who lived after Abdul Kodir al-Jailani. Third; many terms engaged in this Tafsir have not turned out into Tasawwuf Scholars discourse in Abdul Qodir Jailani’s period.